Theoretical Foundation and Contingent Logic of History Teaching Practice: From the Perspective of Marxist Humanism - DENG Yu; ZHENG Jiafu (Jiaoshi jiaoyu xuebao)
Marxist humanism is a way of thinking and a theoretical doctrine based on the historical and practical activity of human beings, confirming the world of the human being and focusing on the emancipation and promotion of the subjectivity of human beings. It is deeply related to history and history teaching. The history under the Marxist humanism can be viewed from the perspectives of individual history and history as a whole. Individuals in history are the "real people" and "social people" in the past. The creation of history as a whole is based on "human needs" and its development depends on "human development". The Marxist humanist perspective on the individual in history and the collective whole of history provides the theoretical foundation and logical direction for history teaching practice. The normative logic of history teaching practice lies in: grasp the principle of individual understanding to construct historical scenarios; adhere to the principle of holistic cognition to present relevant historical materials in various aspects; attach importance to the principle of causal interpretation to clarify the historical causal relationships; and follow the principle of the historical perspective dominates to understand the development of history in a dialectical manner.